2006
DOI: 10.1373/clinchem.2006.068114
|View full text |Cite
|
Sign up to set email alerts
|

Results and Feasibility of an External Quality Assessment Scheme for Self-Monitoring of Blood Glucose

Abstract: Background:The analytical quality of self-monitoring of blood glucose (SMBG) is not satisfactory, and the need for standardized control routines for SMBG has been underscored. The objective of this study was to investigate whether an external quality assessment scheme (EQAS) designed for office laboratories could improve the quality of SMBG measurements. Methods: From October 2001 through March 2004, we conducted 6 glucose surveys for diabetes patients and coordinated them with an EQAS for office laboratories.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…The obtained results depended on the control material employed and were less favorable than the results of Kristensen and colleagues. 20 Imprecision CV across various glucose meters ranged from 2.2 to 12.9% for artificial control samples, 3.66 to 12.9% for plasma control samples, and 4.74 to 12.8% for conserved blood. The author concludes that, at present, EQA surveys are suitable for checking the imprecision of POCT glucose analyzers only.…”
Section: External Quality Assessmentmentioning
confidence: 97%
“…The obtained results depended on the control material employed and were less favorable than the results of Kristensen and colleagues. 20 Imprecision CV across various glucose meters ranged from 2.2 to 12.9% for artificial control samples, 3.66 to 12.9% for plasma control samples, and 4.74 to 12.8% for conserved blood. The author concludes that, at present, EQA surveys are suitable for checking the imprecision of POCT glucose analyzers only.…”
Section: External Quality Assessmentmentioning
confidence: 97%
“…The presence of galactose did not affect the results of glucose concentration mea surements [145]. Kristensen et al demonstrated in 2006 that the introduction of an external quality control system increased the reliability of the results of determination of blood glucose obtained by patients at home by procedures using test strips [146].…”
Section: 11mentioning
confidence: 99%
“…The regulatory bodies need to consider tightening the acceptable minimal standard of accuracy [2,4,14,48,49] and precision for all glucose meters. Strip lots should also be randomly tested by an independent, scientifically based, regulatory entity for efficacy, and the results should be made available to the public in a timely manner.…”
Section: Recommendations For Changementioning
confidence: 99%